Efficacy and safety of modified dual knife fistulotomy in complex ERCP cases involving type 3 papilla - Li, Qinkai; Qian, Mingjie; Cai, Wei; Qiao, Zhenguo; Zhu, Jianhong (Frontiers in Surgery, 2025)
ObjectivesCannulating protruding or pendulous type 3 papilla presents a higher level of difficulty in ERCP. Although pre-cutting papillotomy is a viable strategy, it is not without challenges. To overcome this issue, we developed a modified dual knife fistulotomy technique. The primary objective of this study was to assess the feasibility of a modified dual knife fistulotomy technique for achieving challenging biliary cannulation in type 3 papilla.MethodsThis retrospective study investigated consecutive patients who underwent ERCP and dual knife fistulotomy for challenging biliary cannulation from 2017 to 2023. The study assessed the rates of technical success and adverse events related to dual knife fistulotomy during ERCP.ResultsDuring the study period, a total of 380 patients with native type 3 papilla underwent ERCP. The initial success rate of biliary cannulation using the standard cannulation approach alone was 81.3% (309/380), which improved to 94.5% (359/380) by incorporating the double guidewire technique. Furthermore, the success rate further increased to 99.7% (379/380) with the addition of dual knife fistulotomy. Dual knife fistulotomy achieved a technical success rate of 95.2% (20/21) while no serious adverse events occurred.ConclusionDual knife fistulotomy is an effective technique for gaining access to the biliary system in cases of unsuccessful standard cannulation of type 3 papilla, with no significant increase in the risk of adverse events.